2013
DOI: 10.6004/jnccn.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer

Abstract: These NCCN Clinical Practice Guidelines in Oncology for Cervical Cancer focus on early-stage disease, because it occurs more frequently in the United States. After careful clinical evaluation and staging, the primary treatment of early-stage cervical cancer is either surgery or radiotherapy. These guidelines include fertility-sparing and non-fertility-sparing treatment for those with early-stage disease, which is disease confined to the uterus. A new fertility-sparing algorithm was added for select patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 199 publications
1
81
1
Order By: Relevance
“…2 The standard treatment modality for patients affected by locally advanced cervical cancer consists in chemoradiation. 3 Notwithstanding, accumulating data support the utilization of neoadjuvant chemotherapy (NACT) followed by radical surgery. 4,5 While waiting the results from a multicenter randomized trial comparing chemoradiation versus NACT followed by radical surgery in patients with stage IB2-IIB cervical cancer (EORTC protocol 55994), several investigations have demonstrated that NACT administration is effective in reducing primary tumor diameter, thus allowing radical surgery (type C/type III radical hysterectomy).…”
Section: Introductionmentioning
confidence: 99%
“…2 The standard treatment modality for patients affected by locally advanced cervical cancer consists in chemoradiation. 3 Notwithstanding, accumulating data support the utilization of neoadjuvant chemotherapy (NACT) followed by radical surgery. 4,5 While waiting the results from a multicenter randomized trial comparing chemoradiation versus NACT followed by radical surgery in patients with stage IB2-IIB cervical cancer (EORTC protocol 55994), several investigations have demonstrated that NACT administration is effective in reducing primary tumor diameter, thus allowing radical surgery (type C/type III radical hysterectomy).…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to use resource-stratified guidelines and costeffectiveness as the basis for treatment algorithms (e.g., Breast Health Guidelines International (BHGI) for breast cancer [9] and National Comprehensive Cancer Network (NCCN) for cervical cancer [10]). Centralizing complex surgical procedures that are highly resource and infrastructure-dependent to a central training center, and initially scaling up only the less complex surgical procedures to district hospitals will lead to a sustainable and cost-efficient approach to expansion (Fig.…”
Section: Select a Surgical Intervention Model That Is Safe Achievablmentioning
confidence: 99%
“…In present study, it has been tried to compare the compliance to and toxicity of weekly cisplatin 40 mg/m 2 and three weekly cisplatin 75 mg/ m 2 concurrent with radiotherapy [5]. A possible hypothesis of this study is that the higher peak concentration of cisplatin may be more critical in enhancing synergy of chemoradiation than the weekly cisplatin exposure [8,9].…”
Section: Introductionmentioning
confidence: 97%
“…In countries like India, the disease most often diagnosed in advanced stage when the disease has already spread to adjacent structures including vagina, paracervical and paravaginal soft tissues, urinary bladder and rectum and by this time pelvic lymph nodes are also involved in 20-25% cases [3,4]. A combined modality approach is necessary for the management of patients with cervical cancer [5]. For locoregionally advanced disease (stage IIB, III, IVA) radiation therapy is the primary treatment modality with or without chemotherapy [1].…”
Section: Introductionmentioning
confidence: 99%